Identification and molecular cloning of a functional GDP-fucose transporter in Drosophila melanogaster. - Lühn, K; Laskowska, A; Pielage, J; Klämbt, C; Ipe, U; Vestweber, D; Wild, M (2004)
Nucleotide sugar transporters play a central role in the process of glycosylation. They are responsible for the translocation of nucleotide sugars from the cytosol, their site of synthesis, into the Golgi apparatus where the activated sugars serve as substrates for a variety of glycosyltransferases. We and others have recently identified and cloned the first GDP-fucose transporters of H. sapiens and C. elegans. Based on sequence similarity, we could identify a putative homolog in Drosophila melanogaster showing about 45% identity on protein level. The gene (CG9620) encodes a highly hydrophobic, multi-transmembrane spanning protein of 38.1 kDa that is localized in the Golgi apparatus. In order to test whether this protein serves as a GDP-fucose transporter, we performed complementation studies with fibroblasts from a patient with LADII (leukocyte adhesion deficiency II) which exhibit a strong reduction of fucosylation due to a point mutation in the human GDP-fucose transporter gene. We show that transient transfection of these cells with the Drosophila CG9620 cDNA corrects the GDP-fucose transport defect and reestablishes fucosylation. This study gives experimental proof that the product of the in silico identified Drosophila gene CG9620 serves as a functional GDP-fucose transporter.